Highly fluorescent one-handed nanotubes assembled from a chiral asymmetric perylene diimide1. Issue 20 (11th March 2015) - Ma, Xiaojie; Zhang, Yibin; Zheng, Yingxuan; Zhang, Yifan; Tao, Xia; Che, Yanke; Zhao, Jincai
<x xml:space="preserve">Abstract</x> Highly fluorescent bilayer nanotubes with a right- or left-handed helical sense were assembled from a chiral asymmetric perylene diimide.